Design System for Education & Health Counseling (E-Pedakos) Posyandu in Indonesia Based E-Learning - Wiharto, W; Suryani, Esti; Fatimah, Siti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
The model system of education and maternal and child health counseling at the Posyandu has been done with the direct model, namely Posyandu. The increasing number of women working population affects the lessening number of participants as well as the effectiveness of this activity. This study proposed a model of maternal and child health education and counseling based on e-learning with a reference of electronic education and health counseling (e-pedakos). This study was conducted in several stages. The first stage was the establishment and development of e-pedakos systems and infrastructure. Subsequently, it was examined related to the public’s attendance and responses, which was preceded by the training on how to use E-pedakos. The last stage was the survey on system effectiveness. This counseling model counseling of e-pedakos provides an alternative to resolve the weaknesses of conventional posyandu. It promotes maternal education and counseling which can be done anytime and anywhere.